Cyberspace and international relations : Theory, prospects and challenges - Muller, Benedikt; Kremer, Jan-Frederik (Springer Berlin Heidelberg, 2014)
Cyberspace is everywhere in today's world and has significant implications not only for global economic activity, but also for international politics and transnational social relations.  This compilation addresses for the first time the "cyberization" of international relations - the growing dependence of actors in IR on the infrastructure and instruments of the internet, and the penetration of cyberspace into all fields of their activities. The volume approaches this topical issue in a comprehensive and interdisciplinary fashion, bringing together scholars from disciplines such as IR, security studies, ICT studies and philosophy as well as experts from  everyday cyber-practice. In the first part, concepts and theories are presented to shed light on the relationship between cyberspace and international relations, discussing implications for the discipline and presenting fresh and innovative theoretical approaches. Contributions in the second part  focus on specific empirical fields of activity (security, economy, diplomacy, cultural activity, transnational communication, critical infrastructure, cyber espionage, social media, and more) and address emerging challenges and prospects for international politics and relations.